Identifikasi Reservoir Rekahan Alami Lapangan âAnfieldâ dengan Menggunakan Metode Amplitude Variation with Azimuth (AVAZ) - , Wiji Raharjo, Prof. Dr. Sismanto, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2013)
It has been done a seismic data processing to identify natural fracture reservoir in âAnfieldâ field. This field is located in North West Java Basin with reservoir at metasediment rock. Fracture identification is needed to find hydrocarbon reservoir. This study used Amplitude Variation with azimuth (AVAZ) method. This method is used to determine amplitude variant with receiver azimuth. CDP gather data and well log data located in âAnfieldâ Field are used in this study. Workflow in this study were velocity analysis, running PSTM isotropic, calculating anisotropic parameter, running PSTM anisotropic and AVO inversion. The result showed that âAnfieldâ Field has anisotropic gradient which indicate amplitude anomalies at time slice 2272 ms and showed the presence of hydrocarbon. Fault extraction shows that fault have azimuth orientation 166,220 from north, so that fracture orientation 256,220.